Comparative Analysis of RCEP and WTO Dispute Settlement Mechanisms in International Commercial Relations - Najwa, Sayyid Nabil Mahakim; Fitriyanti, Fadia (International Journal of Business, Law, and Education, 2026)
This article examines the dispute settlement mechanisms under the Regional Comprehensive Economic Partnership (RCEP) and the World Trade Organization (WTO) through a comparative legal analysis. The study aims to assess how both frameworks regulate international commercial disputes and promote legal certainty in cross-border trade relations. Employing a doctrinal and comparative legal approach, this research analyzes treaty provisions, institutional structures, procedural stages, and enforcement mechanisms governing dispute resolution under RCEP and the WTO Dispute Settlement Understanding. The findings indicate that while the WTO provides a more institutionalized and legally binding mechanism, RCEP emphasizes flexibility, consultation, and regional consensus. This article argues that RCEP’s dispute settlement mechanism may complement the WTO framework by offering an alternative forum for resolving international commercial disputes, particularly within the Asia-Pacific region.